ANALISIS KUANTITATIF DAN KUALITATIF EFEK SAMPING OBAT DI RS JANTUNG DAN PEMBULUH DARAH HARAPAN KITA PERIODE JANUARI – JUNI 2021 - Dinda Kusuma Hardini; Silvia Wahyu Widiarti; Saur Lumongga (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Adverse drug reactions are undesirable effects that can be harmful or detrimental after medication administration when dosage and way of administration are in accordance with the purpose of treatment. Identification of the most common type of adverse drug reaction in Rumah Sakit Jantung dan Pembuluh Darah Harapan Kita (RSJPDHK) was executed through Adverse Drug Reactions Monitoring from January to June 2021. The aim of this study is to obtain real data on adverse drug reactions for the purpose of educating medical colleagues in order to reduce similar adverse drug reactions. The designs of this study were qualitative descriptive research (using Naranjo Algorithm) and quantitative. The number of incoming reports were 102. The reports came from inpatient and outpatient wards. The most common form of adverse drug reactions occurred during this period were gastrointestinal bleeding (31.37%) and prolonged INR (International Normalized Ratio) without sign of bleeding (25.49%). Utilisation of blood-thinning medications that cause bleeding, specifically were warfarin, aspirin, and clopidogrel. The results of the qualitative analysis for the highest incidence of adverse drug reactions in the study period were gastrointestinal bleeding with a Naranjo score of 5-8 and the number was 69.77%. The incidence of adverse drug reactions caused by anticoagulants and antiplatelets are quite high even though these two types of medications are the most widely used in RSJPDHK. Socialization of the results of these reports on a regular basis to medical colleagues is necessary in order to reduce the incidence of adverse drug reactions in RSJPDHK.